Treatment for acute bronchiolitis before and after implementation of new national guidelines: a retrospective observational study from primary and secondary care in Oslo, Norway - Mette Brekke; Odd Martin Vallersnes; Nicolai Klem; Håvard Ove Skjerven; Beate Nilsen (BMJ Publishing Group, 2021)
Background Acute bronchiolitis treatment guidelines changed in Norway in 2013, no longer recommending the use of nebulised epinephrine. We aimed to assess whether these changes were successfully implemented in both primary and secondary care. Secondary aims were to compare the difference in management of acute bronchiolitis patients in primary and secondary care between 2009 and 2017.Methods We retrospectively registered data on demographics, clinical features and management from electronic medical records of all infants (<12 months of age) diagnosed with acute bronchiolitis at a primary care centre (Oslo Accident and Emergency Outpatient Clinic) and a secondary care centre (Oslo University Hospital) in Norway in 2009, 2014 and 2017. All patient records were individually reviewed to ensure data accuracy.Results We included 680 (36.3%) patients from primary care and 1195 (63.7%) from secondary care. There was a reduction in the use of nebulised epinephrine from 2009 to 2017 from 66.9% to 16.1% of cases (p<0.001) in primary care and from 59.1% to 4.9% (p<0.001) in secondary care. In parallel, there was an increase in the use of nebulised saline treatment, from 0.8% to 53.8% (p<0.001) in primary care and from 39.3% to 65.3% (p<0.001) in secondary care. The decrease in the use of nebulised racemic epinephrine occurred earlier in secondary care than in primary care; 13.4% vs 56.1%, respectively, in 2014.Conclusions Implementation of the new guidelines on the treatment of acute bronchiolitis was successfully implemented in both primary and secondary care.